The label “Cação” is a shark or a ray and can be a threatened species! Elasmobranch trade in Southern Brazil unveiled by DNA barcoding - Bernardo, Cristina (2020)
Sharks exhibit peculiar characteristics, which may lead to overfishing to cause irreversible damage to stocks and failing to restore original population sizes. Although global fin trade has decreased since 2000 meat trade has increased, with Brazil figuring as the largest shark meat importer worldwide. Still, in Brazil, elasmobranchs are traded under the label “cação” making it difficult to monitor what species are actually being traded. To overcome elasmobranch fraudulent trade, molecular techniques have been developed aiding in illegal trade monitoring. Therefore, the objective of the present study was apply DNA barcoding technique (COI analysis) as a molecular support tool for the identification of shark species commercialized in the main fish markets of southern Brazil. A total of 650 base pairs (bp) of barcode COI from 231 samples were sequenced and analyzed, identifying 16 different elasmobranch species, being 12 shark species and four batoid species. About 43.3% of the total sampled consists of species listed in some IUCN risk category (e.g. Carcharias taurus, Carcharhinus falciformis, Sphyrna lewini, S. zygaena, Squatina guggenheim). A key step for conservation would be encourage the consumer to demand the correct identification of the meat consumed. Such an attitude may influence the decision of supermarkets and fish markets to purchase only correctly identified products, which in turn would lead to the need for specialists actively and constantly working alongside fishery landings.